Aktivitas Fisik dengan Status Gizi Remaja di SMP Negeri 25 Surabaya - Aulia Rochmah; Siti Rahayu Nadhiroh (Media Gizi Kesmas, 2024)
Background: Physical activity is an action taken by individuals from waking up to resting. Physical activity is very important in order to maintain a healthy body and ideal body weight. Increasing levels of life and technological advances have triggered changes in the way of life or habitual patterns of life. The existence of a contemporary culture with the support of the latest innovations can lead to reduced physical activity. Lack of physical activity can lead to an increased risk of BMI (Body Mass Index). To ensure that adolescents achieve an ideal weight and maintain physical health, it is imperative that they increase their physical activity levels. Objectives: This study aims to determine the relationship between physical activity and the nutritional status of adolescents at State Junior High School 25 Surabaya. Methods: This type of research is observational with a cross-sectional study design. The sample of this research is 80 respondents. Data analysis in this study consisted of univariate and bivariate with Chi-Square. Results: The study result indicated that 42.5% of students have normal nutritional status and 77.5% of students do light physical activity. Based on bivariate analysis, it was found that there was a significant relationship between physical activity and the nutritional status of adolescents at State Junior High School 25 Surabaya (p-value = 0.008). Conclusions: There is a significant relationship between physical activity and the nutritional status of adolescents at SMP Negeri 25 Surabaya. It is recommended to measure and weigh body weight every week by trained officers  to be able to monitor each individual's nutritional status and carry out regular physical activity.